Les hindous de Karachi dans la perspective historique.De la domination socio-économique à la marginalisation minoritaire - Michel Boivin (Revue des Mondes Musulmans et de la Méditerranée)
The Hindus are said to be between 500 000 and one million in Karachi. Before partition, the Hndus were in majority in the city but after 1947, most of them migrated to India where they settled. After this very important shifting, they became a religious minority in the newly born Pakistan. The first part of the paper will deal with their situation before partition, especially their organisation, their relation with other religious communities, the role they played in the modernisation of the city, and finally how they put their mark on the urban territory. The topic of the second part will be partition. After analysing to what extent the Hindus took part in nationalist fight, it will be necessary to study the conditions in which migration to India occurred, and what were the new conditions of life for the Hindus who stayed in Karachi. Even if the Hindus low castes were to reinforce the process of “ghettoisation”, no major change happened in the organisation of the urban territory. The last part will be devoted to the present situation of the Hindus in Karachi. What are their relations with the government, national as well as provincial? The cult and the Hindu practise will be studied and the transmission of religious knowledge, where caste associations played a leading role.